EthicAI=Labs - Koutsomichalis, Marinos (My University, 2022)
The project aiming to create a cross-genre space for critical conversation on AI and ethics in Southeast Europe had the chance to fulfil this via various actions that help the project fellows to meet in person and to create close contact and collaboration.
Keywords: Artificial intelligence; Ethics